Psychosocial Factors Correlated with Cooperation Skills in New Normal of Undergraduate Students - Sakdapat, Naksit (Journal of Behavioral Science for Development, 2023)
This study is a comparative study using the interactionism model. It aims to identify significant indicators and predict the volume of psychological states and situational factors related to cooperation skills in the new normal. The study sampling group is 789 undergraduate students selected by multi-stage sampling. The study found that attitude towards the development of work skills in the new normal life are positive and significant to cooperation skills (r = 0.605, p<.01) The multiple regression analysis found that psychological traits, situational factors and psychological states can predict cooperation skills of the sampling group by 52.97% the best predicting factor is an ability to learning process within the university. The high-risk groups include undergraduate male students, low-grade undergraduate students and old undergraduate students. The results of this research have suggested ways to develop cooperation skills and encourage students to prepare and develop cooperation skills more effectively. The researcher has also been used to create a new set of manuals for developing cooperation skills and training courses to develop additional potential under the project “preparing to enter the working age in the new normal”.